Interaction Between PbF2 and EuS in Saline Melt NaCl-KCl - Zinchenko, V.; Nechyporenko, G.; Koshkina, L. (Physics and Chemistry of Solid State, 2016)
Ability to interaction between PbF2 and EuS in NaCl-KCl saline melt is established by methods of luminescent spectroscopy and the X-ray diffraction analysis. Mutual quenching of intensive blue luminescence of Eu2+ and, partially, of yellow luminescence of PbF2 in the solidified solutions-melts on the basis of NaCl-KCl is observed, that confirms exchange reaction with formation of PbS particles. Formation of abnormal phases "NaCl" and "KCl" with the changed parameters of lattices, and also of PbFCl phase is revealed, and also possibility of occurring phases of PbS, β - PbF2 and NaF in separate specimens is not excluded.